An Assessment of the Variation in the Areal Extent of Laguna Santa Rosa, A Protected Wetland in Atacama Region of Chile - Alam-, M (Springer Nature, 2025)
The objective of the present study is to evaluate the variation of the areal extent of Laguna Santa Rosa (LSR), a wetland located in the Atacama Region of Chile protected under the Ramsar Convention over a decade (1993–2014), to determine its cause(s) and mechanism(s). To accomplish this objective, the following tasks were undertaken: analysis of the variation in the areal extent of the wetland through Landsat-5 TM satellite images, delineation of the natural (viz. extreme weather events) and anthropic factors (viz. mining) responsible for delimiting the transgression and regression of this wetland, and projection of future trends based on available information about natural phenomena and anthropogenic activities in the area. A decreasing trend with occasional fluctuations in the areal extent of LSR observed between 1993 and 2014 was punctuated by extreme rainfall and consequent flood following accumulated precipitation exceeding 40 mm in a single day and hourly mean rainfall rates higher than 10 mm/h at several locations in the arid Atacama Region on March 25, 2015. This increased the areal extent of LSR, as observed in the satellite images of 2016–2017 following the extreme weather event of 2015. On the other hand, groundwater extraction for ongoing copper and gold mining operations in the Maricunga Basin, which is responsible for the general decreasing trend in the areal extent of LSR, as observed between 1993 and 2014, is going to increase manifold with the use of water rights issued for the already approved three lithium mining projects in the Maricunga salt flat, to whose southern end LSR is located. The interplay of the effects of extreme weather events and groundwater extraction for mining activities in the area makes assessing the latter’s impact rather complex and restricted to the intervals between successive extreme weather events. This is why the selected period precedes the extreme weather event of 2015, which was followed by another such event in 2017. Apart from the extreme weather events, occasional areal extent increase of this groundwater-dependent wetland could also be caused by a halt in groundwater extraction in the event of suspension of mining activities for a considerable period. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.